2007
DOI: 10.1089/cpb.2007.9986
|View full text |Cite
|
Sign up to set email alerts
|

Benefiting from Social Capital in Online Support Groups: An Empirical Study of Cancer Patients

Abstract: With measures specific to the online cancer environment and data from an online survey of cancer patients, the current study finds support for the following model: asynchronous online communication Ǟ social interaction Ǟ social support Ǟ positive health outcomes in terms of stress, depression, and coping. The findings suggest that the Internet can be a positive cyber venue for cancer patients as they confront illness, undergo treatment, and seek out support. 587

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(101 citation statements)
references
References 20 publications
5
89
0
7
Order By: Relevance
“…On the other hand, the levels of social capital within U.S. communities appear to decline as the population continues to age. Previous study has found that social capital is associated with health outcomes such as mental health (Scheffler, Brown, & Rice, 2007), obesity and diabetes (Holtgrave & Crosby, 2006), and cancer (Beaudoin & Tao, 2007). Rostila (2011) argued that social resources can reduce both physical and psychological health problems by serving as a physiological triggering mechanism, strengthening people's immune system to fight disease and buffer stress.…”
Section: Social Capital and Successful Agingmentioning
confidence: 99%
“…On the other hand, the levels of social capital within U.S. communities appear to decline as the population continues to age. Previous study has found that social capital is associated with health outcomes such as mental health (Scheffler, Brown, & Rice, 2007), obesity and diabetes (Holtgrave & Crosby, 2006), and cancer (Beaudoin & Tao, 2007). Rostila (2011) argued that social resources can reduce both physical and psychological health problems by serving as a physiological triggering mechanism, strengthening people's immune system to fight disease and buffer stress.…”
Section: Social Capital and Successful Agingmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Online communities are not ''information vending machines,'' 1 but sites where individuals exchange information as well as provide emotional support and develop relationships 1,8,9 such that individuals become better able to cope, 9,10 feel more confident in their knowledge, and experience better health outcomes. [8][9][10] With young adults living increasingly digital lives, [11][12][13] online support presents opportunities to provide much-needed resources to those seeking them. As health-information research suggests, ''with Internet usage so prevalent among teenagers and young adults, development of age-appropriate web-based resources has great potential,'' especially in youth-focused areas like adolescent and young adult (AYA) oncology.…”
Section: Introductionmentioning
confidence: 99%
“…14 Despite research advances, little attention has been paid to the role of social-networking in supporting AYAs affected by cancer. Empirical, effect-focused research examining cancer-related online support concentrates on a few cancers with minimal examination of broader diagnoses or demographics, 10,21,22 as is being done here. The current study is an important extension, because it addresses the role messages play in online peer support for a population with well-documented support needs.…”
Section: Introductionmentioning
confidence: 99%
“…35 Broader discussion of social media as a tool for community--building has been advanced within the context of political activity, where social media is identified as a method for organizing civic action and revolutionary protests. 36,37,38 Related research focuses on the online social connections and "virtual communities" developed around common interests such as religion, 39 health, 40 education, 41 social interests and norms, 42 politics, 43 web--video sharing, 44 and reading. 45 In these analyses, social media is framed as an online instrument utilized to draw together offline persons.…”
Section: Literature Reviewmentioning
confidence: 99%